Ecohealth:: research experiences and innovative practices to understand linkages between health, ecosystems and society (Sustainability in Debate, 2018)
Dominique F. Charron (editor). Ecohealth Research in Practice ”“ Innovative Applications of an Ecosystem Approach to Health. Ottawa, ON, Canadá, International Development Research Centre (IDRC) & Springer, 2012. 282 páginas. ISBN: 978-1-4614-0516-0. $179,00 (Hardcover).Fotografias, figuras, gráficos, índice remissivo, lista de colaboradores, mapas, referências bibliográficas, tabelas.